Implementation of Green Economy in Household Environment in Tegal Sari Hamlet, Pademawu, Pamekasan Post-Pandemic - Mohammad Imam Sufiyanto; K Khairunisa; J Jelita; Yenny Suzana; Elce Purwandari (Salus Publica: Journal of Community Service, 2024)
The application of the green economy during the covid-19 pandemic has become a problem in efforts to reduce household waste. Indonesia is currently ranked second as the largest waste producer in the world, one rank below China. The implementation of Community Activity Restrictions (PPKM) in Tegal Sari Village and other Pamekasan city areas has resulted in limited community activities outside the home, many workers being laid off making the community's economy decline, but economic needs are increasing. This can cause food packaging plastic waste produced from households to increase every day. Garbage will accumulate continuously and can even make the environment a hotbed of disease if not managed properly. The creative idea of ​​handicrafts aims to help reduce the level of household waste by sorting waste using 3R (Rescue, Reduce, Recyle). The method used in this study is a qualitative method by interviewing resource persons who have ideas for creating items that are suitable for use from household waste.The method used in this study is the Participatory Action Research (PAR) method with a qualitative approach by interviewing resource persons who have ideas to create suitable items for use from household waste. The result of post-covid-19 pandemic service is that the community can distribute inorganic waste into goods of economic value by restoring the role of the green economy so that solutions from waste can be overcome.